Intelligent internet of things for smart healthcare systems - Srivastava, Durgesh (Computer scientist); Sharma, Neha (Computer scientist); Sinwar, Deepak; Yousif, Jabar H.; Gupta, Hari Prabhat (Boca Raton : CRC Press, 2023)
"The book focuses on developments in AI and IoT integration for smart healthcare, with an emphasis on current methodologies and frameworks for the design, growth, implementation, and creative use of such convergence technologies to provide insight into smart healthcare service demands. Concepts like signal recognition, computation, internet of health stuff, and so forth and their applications are covered. Development in connectivity and intelligent networks allowing for social adoption of ambient intelligence are also included. Features: Introduces Intelligent IoT as applicable to key areas towards smart healthcare. Discusses computational Intelligence and IoT based optimizations of smart healthcare systems Explores effective management of healthcare systems using dedicated IoT based infrastructures Includes dedicated chapters on securing patient's confidential data Reviews diagnosis of critical diseases from medical imaging using advanced deep learning-based approaches This book is aimed at researchers, professionals and graduate students in intelligent system, big data, cloud computing, information security, and healthcare systems"--
Internet of Things in Smart & Intelligent Health care System / Akarsh K Nair and Jayakruhsna Sahoo -- Applications of Intelligent Internet of Things for Smart Healthcare Systems / Rohit Mittal, Vibhakar Pathak, Amit Mithal -- Technological Shift of Healthcare System Using Internet of Things (IoT) / Gauri Shanker Gupta, Shishir Singh Chauhan, Mrinal Kumar Pathak and Rakesh Kumar Sinha -- IoT-Based Smart Healthcare System (SHCS) : Big Data Mangement And Information Security Using Cloud Data Governance / Dr Shantha Visalakshi Upendran -- Information Security and Data Management for IoT Enabled Smart Healthcare / Maram Bani Younes and Nameer N. El-Emam -- AI-assisted Big Data Analytics for Smart Health Care Systems / Akruti Sinha, Devika Sapra, Gaurav Gaurav, Mahin Anup and Deepak Sinwar -- Cloud computing assisted real-time health monitoring and tracking / Amro Al-Said Ahmad and Nameer N. El-Emam -- A Big Advancement In Healthcare : Supervision Of Worldwide Healthcare Through An Iot-Based System / Santosh Kumar Srivastava, Hare Ram Singh, Sunil Kumar Maakar, Durgesh Srivastava, Praveen Kantha -- Examine the Semantic similarity based on Association measurement among biomedical concepts in Health Domain / Ahmad. K. Alkayed and Abdelhakeem Abdelrahman -- Internet of things (IoT) : An emerging approach for Pharmaceutical and Healthcare system / Dr. SmritiOjha, Sudhanshu Mishra, Akhalesh Kumar and Disha Sharma -- Blockchain technology implications for healthcare systems using the Internet of Things : A systematic Literature review / Maryam Aljabri and Jabar H. Yousif -- Deep Learning Approach for Classification of Alzheimer's disease / Abbas H. HassinAlasadi and Faten Salim Hanoon -- Plant Disease identification using Convolution Neural Network / Dipra Mitra, Shikha Gupta, Durgesh Srivastava, Sudeshna Sani -- An Accurate Study of the Quality of Health Coinciding with the Process of Handwriting / Atika Fatma and Shivam Tiwari -- E-nose sensors applications and challenges in the health sector / Sanad Al-Maskari, Saeid Hosseini, Eimad Abusham.
OCLC-licensed vendor bibliographic record.
Keywords: Medical informatics; Medical technology; Internet of things; Artificial intelligence -- Medical applications; COMPUTERS / Machine Theory; COMPUTERS / Computer Engineering; TECHNOLOGY / Electricity